Cognitive, language, and school performance in children and young adults treated for low‐grade astrocytoma in the posterior fossa in childhood. Issue 3 (7th July 2021) - Kristiansen, Ingela; Eklund, Cristina; Strinnholm, Margareta; Strömberg, Bo; Törnhage, Maria; Frisk, Per
Abstract: Background: Pilocytic astrocytoma is the most common brain tumour type in childhood located in the posterior fossa, and treated mainly with surgery. These tumours have low mortality, but knowledge concerning its long‐term outcome is sparse. Aim: The aim of this study was to investigate whether children treated for pilocytic astrocytoma in the posterior fossa had late complications affecting cognition, language and learning. Methods: This descriptive single‐centre study includes eight children and 12 adults treated as children for pilocytic astrocytoma in the posterior fossa, with a mean follow‐up time of 12.4 (range 5–19) years. Well‐established tests of intelligence, executive, language and academic function were used. Results: Intelligence tests showed average results compared with norms. Five patients scored <−1 SD (70–84) and 3 low average (85–92) on full scale IQ. The patients scored average on subtests regarding executive function, except for significantly lower results in inhibition/switching (p = .004). In Rey complex figure test half of the patients scored below −1 SD. Language tests were normal except for significantly lower results in naming ability (p = .049) and in inference (p = .046). In academic tests, results were average, except for significantly lower results in reading speed (p = .024). Patients with learning difficulties performed worse in the tests. Conclusions: The patients' functional outcome was favourable but, a not‐negligible part of the patients displayed neurocognitive difficulties as revealed by extensive neuro‐cognitive and academic testing. Thus, it is important to identify those in need of more thorough cognitive and pedagogic follow‐up programmes, including school interventions.